IL-3 Up-regulates and Activates Human Eosinophil CD32 and αMß2 Integrin Causing Degranulation - Esnault, Stephane (Clin Exp Allergy, 2017)
BACKGROUND: Eosinophils contribute to the pathogenesis of multiple diseases, including asthma. Treatment with antibodies targeting IL-5 or IL-5 receptor α reduces the frequency of asthma exacerbations. Eosinophil receptors for IL-5 share a common ß-chain with IL-3 and GM-CSF receptors. We recently reported that IL-3 is more potent than IL-5 or GM-CSF in maintaining the ERK/p90S6K/RPS6 ribosome-directed signaling pathway, leading to increased protein translation. OBJECTIVE: We aimed to determine disease-relevant consequences of prolonged eosinophil stimulation with IL-3. METHODS: Human blood eosinophils were used to establish the impact of activation with IL-3 on IgG-driven eosinophil degranulation, which was then compared to IgG-mediated degranulation of freshly isolated (unstimulated) airway eosinophils activated in vivo by segmental allergen challenge. RESULTS: When compared to IL-5, continuing exposure to IL-3 further induced degranulation of eosinophils on aggregated IgG via increased production and activation of both CD32 (low affinity IgG receptor) and αMß2 integrin. In addition, unlike IL-5 or GM-CSF, IL-3 induced expression of CD32B/C (FCGRIIB/C) subtype proteins, without changing CD32A (FCGRIIA) protein and CD32B/C mRNA expression levels. Importantly, these in vitro IL-3-induced modifications were recapitulated in vivo on airway eosinophils. CONCLUSIONS: We observed for the first time upregulation of CD32B/C on eosinophils, and identified IL-3 as a potent inducer of CD32- and αMß2-mediated eosinophil degranulation.